First-order linear partial differential equations in the class of separately differentiable functions - Myronyk, V.I.; Mykhaylyuk, V.V. (Carpathian Mathematical Publications, 2013)
It is obtained a general solution of first-order linear partial differential equations in the class of separately differentiable functions.